Quartz luminescence sensitivity as a sediment provenance tracer: perspectives from the Northern Andes Orogenic basins - Ortiz Barrios, Carlos Andres (2024)
In recent years, the luminescence of quartz has emerged as a potential tool for provenance analysis, particularly through the application of optically stimulated luminescence (OSL) sensitivity. While OSL sensitivity in quartz crystals from igneous and metamorphic rocks is typically low, previous findings indicate that OSL sensitivity can vary within five orders of magnitude within Quaternary sediments. These observations imply that quartz sensitization, in natural settings, occurs at some stage between the sediment source areas and the depositional sites. Laboratory experiments have demonstrated that sensitization of the quartz OSL fast component can be prompted by irradiation-bleaching cycles or by heating at temperatures above 300 °C. These sensitization mechanisms could be driven by surface processes that expose quartz grains to ionizing radiation and sunlight or to high temperatures, including sediment reworking, soil mixing, and wildfires. Thus, the longer sediments remain on the Earths surface, the higher the probability of those grains undergoing sensitization through surface processes. In this way, the extended residence of sediments on the surface increases the opportunities for quartz grains to experience natural irradiation, bleaching by sunlight exposure, and heating, increasing the probability of sensitization. This hypothesis establishes a connection between OSL sensitivity and surface processes occurring mainly in the source areas, ultimately enabling the tracing of the provenance of sediments released from particular source areas characterized by a specific combination of source rock and surface processes. OSL sensitivity has been effectively utilized for provenance analysis in modern deposits, but its application in ancient basin-fill sequences has been limited. This dissertation aims to address this gap by investigating the OSL sensitivity of pure quartz sand grains extracted from sandstones of a ~10 km-thick exhumed crustal section of the Northern Andes in the Colombian Eastern Cordillera, as well as from one of its adjacent basins. The studied section encompasses rocks from the entire Phanerozoic eon that have a well-established provenance history determined through various methods including low-temperature thermochronology, detrital geochronology, and sandstone petrography. This comprehensive array of information provides a strong foundation to establish a proof-of-concept for the applicability of quartz OSL sensitivity as a sediment provenance tracer. To achieve this, in this work the OSL sensitivity, measured in sandstones from the Colombian Eastern Cordillera, is compared with proxies such as detrital zircon U-Pb geochronology and sandstone petrography. Here, two different scenarios within the same basin in the Northern Andes were tested. Firstly, changes in quartz OSL sensitivity were demonstrated to be correlated with changes in sediment source areas characterized by contrasting conditions related to the residence time that quartz grains spend on the Earths surface. Low-sensitivity quartz is associated with orogenic source areas experiencing rapid exhumation and denudation, whereas quartz exhibiting higher sensitivity is correlated with stable cratonic source areas. Finally, the highest-sensitivity quartz is linked to the recycling of sedimentary rocks that exhibit enhanced quartz OSL sensitivity. These observations allow for the construction of a hypothetical frame that serves as a basis for using the quartz luminescence sensitivity as a provenance tracer not only on quaternary and modern sediments but also in ancient basin-fill sequences.